Comparison of serum and plasma specimens for syphilis serology using the reagin screen test. - Dyckman, J D (1980)
One serum and three plasma samples were obtained from each of 125 normal individuals and from 140 patients with treated or untreated syphilis. Serum samples were tested by the Venereal Disease Research Laboratory (VDRL) test and by the Reagin Screen Test (RST). Plasma specimens were tested only with the RST. When tested within 24 h after collection, all specimens from normal individuals were nonreactive. Plasma specimens from normal individuals stored for up to 72 h after collection continued to yield a clearly nonreactive result in 423 of the 426 samples tested by the RST. Serum and plasma samples from syphilis patients tested within 72 h after collection by the RST yielded qualitative and quantitative results almost identical to results of serum tested by the VDRL test.